FILOSOFI ANGSA PADA BALE BUKUR DALAM UPACARA MAMUKUR DI PURI PEMECUTAN, KOTA DENPASAR - Ni Wayan Murniti (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
The use of bale shaving facilities containing geese symbols and some accessories in them in the implementation of ceremonies especially mamukur in Bali and of course contain the philosophy in them. Based on the results of the study can be described as follows: The shape of the goose is a type of large poultry, which can sort food and be considered purified animals and placement behind the shaving bales. There are several functions of the swan symbol in the bale shave in the mamukur ceremony which can be obtained, among others: the religious function consists of two, namely; function in scale, as a means for placement of puspasarira. The noetic function, as a means of delivering Sang Hyang Atma to the natural world or achieving deliverance. In addition to the function of religion, it also has a cultural function which is an art that has been inherited by the ancestors which implies philosophy and local wisdom. The last function of the swan symbol in the bale shave is the aesthetic function which refers to the concept of satyam (truth), siwam (purity), sundaram (beauty).